Assessment of thinking skills in relation to reading and writing in English among Malaysian university students - Yan, Ziguang (2017)
Thinking skills has been the central aim of education because it not only enables participants to become more successful in learning but for them to discover their own potential in order to contribute to the development of society (Barak, Ben-Chaim, & Zoller, 2007). However, lack of thinking skills is a big issue, especially among graduates. Many employers complained that graduates were merely proficient in academic knowledge but lacked soft skills such as analytical skills (Shakir, 2009). Consequently, the trend of unemployment rate is increasing in Malaysia (The Malaysia Statisitics Department, 2011). This study therefore aimed to investigate the thinking skills performance of the tertiary level participants through their application of thinking skills in a reading comprehension test and a writing test. To achieve the general objective, the study first investigated the participants’ perception of thinking skills that were infused in the classroom instructions. Second, the participants’ thinking skills were investigated in a reading comprehension test and a writing test. Finally, the scores obtained in the reading and writing tests were correlated with the independent variables: departments (Communication, Malay, Foreign languages and English), MUET band scores (lower than 3, Band 3 and Band 4) and scores of reading and writing strategies (low, medium and high). To realize the above objectives, a quantitative method was adopted as the main design of the study. A total of 218 participants were randomly selected from freshmen who were enrolled in the first semester of 2014/2015 in the Modern Languages and Communication Faculty of UPM. Three instruments were used in the study. The first was a set of questionnaire which was developed to obtain results of the participants’ perceptions of the infusion of thinking skills in classroom instructions. The second instrument was a series of reading comprehension test questions that were formulated based on Bloom’s taxonomy. The third instrument was an argumentative essay in which the participants’ employment of thinking skills in the writing test was evaluated. Finally, the data obtained from these instruments was analyzed using SPSS. Based on the results, it showed that majority of the participants strongly believed that thinking skills were infused in the classroom teaching. Generally, in the reading and writing tests, participants’ thinking skills performance was better in lower order thinking skills (LOTS) than in higher order thinking skills (HOTS). In comparing participants’ thinking skills between different departments, the results illustrated that English language department participants obtained a higher median scores in the reading and writing tests compared to other departments’ participants. As for the MUET bands, participants with MUET band 4 obtained higher median scores when compared with participants of other MUET Bands. The results also revealed that the usage of reading and writing strategies did not affect participants’ thinking skills performance in the reading comprehension and writing test. The results of the relationship between students’ thinking skills performance in reading and writing showed a positive co-relation, which means that the more proficient usage of thinking skills in the reading comprehension test, the more proficient application of thinking skills was displayed in the writing test. The results of the study are significant as they provide the evidence that freshmen still need to improve their ability of thinking skills. The development of LOTS and HOTS could not be separated because any inability in the LOTS could affect HOTS. One possible solution, perhaps, is by integrating LOTS and HOTS practices into the teaching and learning of reading and writing by the tertiary institution instructors.